2016
DOI: 10.1097/aap.0000000000000441
|View full text |Cite
|
Sign up to set email alerts
|

Activated Glia Increased the Level of Proinflammatory Cytokines in a Resiniferatoxin-Induced Neuropathic Pain Rat Model

Abstract: Activated glia participate in the pathogenesis of RTX-induced neuropathic pain and are likely to be the source of proinflammatory cytokines. Inhibition of glia contributes to an analgesic effect. These findings provide a novel strategy for the treatment of postherpetic neuralgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…includes activation of glia that induce a state of spinal neuroinflammation, which may reflect the persistent or altered primary sensory neuron input to the central nervous system that promotes the development of central neuroinflammation (Gwak et al, 2012, Ikeda et al, 2012, Trang et al, 2012, Chen et al, 2014, Lei et al, 2016, Liu et al, 2016. Therefore, both peripheral nerve injury and inflammation can upregulate the expression of glia, as marked by increased expression of CD11b or ionized calcium binding adaptor molecule 1 (Iba1) for microglia activation and Glial Fibrillary Acidic Protein (GFAP) for astrocyte activation, in both sensory ganglia…”
Section: Glia and Neuroinflammation The Transition From Acute To Chrmentioning
confidence: 99%
See 1 more Smart Citation
“…includes activation of glia that induce a state of spinal neuroinflammation, which may reflect the persistent or altered primary sensory neuron input to the central nervous system that promotes the development of central neuroinflammation (Gwak et al, 2012, Ikeda et al, 2012, Trang et al, 2012, Chen et al, 2014, Lei et al, 2016, Liu et al, 2016. Therefore, both peripheral nerve injury and inflammation can upregulate the expression of glia, as marked by increased expression of CD11b or ionized calcium binding adaptor molecule 1 (Iba1) for microglia activation and Glial Fibrillary Acidic Protein (GFAP) for astrocyte activation, in both sensory ganglia…”
Section: Glia and Neuroinflammation The Transition From Acute To Chrmentioning
confidence: 99%
“…themselves and in the central nervous system (Ikeda et al, 2012, Romero et al, 2013, M'Dahoma et al, 2015, Liu et al, 2016, Lei et al, 2016. More importantly, pharmacological inhibition of glia has been shown to largely abolish enhanced neuronal excitation in models of chronic pain, suggesting that glial cells are the primary drivers of the neuronal hyperexcitability underpinning painful phenotypes (Ikeda et al, 2012).…”
Section: Glia and Neuroinflammation The Transition From Acute To Chrmentioning
confidence: 99%
“…Spinal cord dorsal horn glial cell signal transduction-induced central sensitization is one of the important pathogeneses of DNPs. The activation of microglia produces and releases a variety of cytokines and excitatory substances of neurons or glial cells [ 2 4 ], promotes NR2B activation on neuronal cells, NR2B is a subunit on NMDA, and increases NMDA-mediated current. NMDA receptor activation can further induce the sensitization of the central nervous system, which is one of the important pathogeneses of DNP [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“… 5 During periods of pain, reactive oxygen species (ROS) are released, which can damage the nerve and induce neuropathic pain. 6 , 7 ROS are also important factors in autophagy. 8 Although research has shown that cellular autophagy can lead to neurodegeneration or neuronal dysfunction, 9 the molecular mechanisms of neuropathic pain are still unknown.…”
Section: Introductionmentioning
confidence: 99%